Evaluation of Efficiency of Drug Storage in Pharmacy Warehouses Of Primary Health Center (PHC): A review - Novia Ariani Dewi; Yuni Andriani; Vera Anggie Almatiin (Journal of health research and technology, 2025)
Primary Health Center (PHC) is a place to provide health services for individuals and public health that requires providing preventive, intensive, curative, and rehabilitative services in community health centers under the supervision of the District/City Health Office. Management of pharmaceutical preparations that begins with planning, requesting, receiving, storing, distributing, controlling, recording and reporting as well as monitoring and evaluation. Drug storage functions to supervise and protect against physical or chemical damage so that it is easy to find, quality can be maintained and drug preparations are not lost or damaged. This study is a review of articles written based on the results of reviewing several articles or literature related to the efficiency of drug storage in pharmacy warehouses. There are several indicators that are still not in accordance with several research results. The efficiency of drug storage in several health center pharmacy warehouses still does not meet the established indicator standards. Drug storage efficiency is very important for the following reasons, namely to maintain patient safety, optimize cost management, facilitate drug accessibility, and improve service quality that will have a positive impact on the agency.